1997
DOI: 10.1183/09031936.97.10112455
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of CT lung density in patients with chronic asthma

Abstract: All subjects underwent CT scanning of the lungs and respiratory function testing within 2 days of each other. In five of the asthmatic patients a CT scan was performed on two occasions before and after treatment with nebulized bronchodilator. In a different group of five asthmatics these measurements were performed at the end of and 6 weeks after an exacerbation.The mean value of the lowest fifth percentile of the CT lung density in the patients with chronic obstructive pulmonary disease (COPD) was -942 (SD 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 30 publications
6
44
2
1
Order By: Relevance
“…The present authors considered that the discrepancy between their and the present results might be because the present subjects were older. In agreement with the present results, BIERNACKI et al [18] observed that patients with chronic stable asthma, as well as COPD, showed a reduction in CT lung density in comparison with controls. However, in five asthmatic patients, they also found no significant differences in the lowest fifth percentile MLD before and after using a nebulised b 2 -agonist as well as at the end of an exacerbation and 6 weeks later.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The present authors considered that the discrepancy between their and the present results might be because the present subjects were older. In agreement with the present results, BIERNACKI et al [18] observed that patients with chronic stable asthma, as well as COPD, showed a reduction in CT lung density in comparison with controls. However, in five asthmatic patients, they also found no significant differences in the lowest fifth percentile MLD before and after using a nebulised b 2 -agonist as well as at the end of an exacerbation and 6 weeks later.…”
Section: Discussionsupporting
confidence: 82%
“…GEVENOIS et al [17] showed that acute expiratory airflow limitation and chronic hyperinflation did not influence mean lung density (MLD) and the relative lung area with an attenuation of v-950 HU (RA950) in nonsmoking asthmatic patients. BIERNACKI et al [18] observed that some patients with chronic stable asthma develop a reduction in CT lung density and that acute or chronic overinflation did not affect the lowest fifth percentile MLD. The presence and significance of decreased attenuation as assessed by CT scan thus remains to be clarified in nonsmoking asthmatics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From a study of life-long nonsmokers with nonatopic asthma, BIERNACKI et al [11] have previously reported that the asthmatics had lower lung computed tomographic (CT) density than the normal controls, whereas no significant correlation was found between CT lung density, and FEV1, KCO, or residual volume (RV)/TLC ratio. PANHUYSEN et al [9] reported from their 25-yr follow-up of asthmatics that 22% of the patients had a postbronchodilator diffusion constant <80% pred, which might suggest disease progression to emphysema, although these patients had higher lifetime tobacco exposure (pack-yrs) than patients with a diffusion constant within the reference range.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis for CT was devised to compensate for this difficulty. Quantitative CT (QCT) methods have beeen mainly used in other specialties, such as cardiology and pulmonology [36][37][38][39][40][41][42][43]. Recent neuroradiological studies, which used densitometry analysis, focused on finding tumors or regional pathological changes [44][45][46][47][48].…”
Section: Technical Implicationsmentioning
confidence: 99%